Importance of extended blood group genotyping in multiply transfused patients - Osman N.H.; Sathar J.; Leong C.F.; Zulkifli N.F.; Raja Sabudin R.Z.A.; Othman A.; Asral Wirda Ahmad Asnawi (Pergamon-Elsevier Science Ltd, 2024)
Indexed by WOS/Scopus/ERA